High-adhesion super-hydrophobic protective coating process method and coating

By using neodymium modified magnetic nano-iron oxide and alternating charge modified polymer microspheres on the steel surface, combined with the modified nano-silica superhydrophobic film layer, the problem of insufficient adhesion of superhydrophobic coating is solved, achieving high Coatings with adhesion and superhydrophobic properties.

CN119406728AInactive Publication Date: 2025-02-11SHANGHAI MARITIME UNIVERSITY

Patent Information

Application Number
CN202411546296.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The superhydrophobic coating lacks adhesion to the steel surface, which causes the coating to fall off easily and cannot effectively realize the protection function.

Method used

Neodymium modified magnetic nano-ferrous oxide is used as the first layer to improve adhesion through magnetic field orientation arrangement and solid solution reaction; then the negative charge modified polymer microspheres and positive charge modified polymer microspheres are alternately coated on its surface. Finally, the modified nanosilicon dioxide superhydrophobic membrane layer was covered.

Benefits of technology

The adhesion and mechanical strength of the superhydrophobic coating on the steel surface is significantly improved, and the stability and durability of the coating are enhanced while maintaining superhydrophobic properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-adhesion super-hydrophobic protective coating process method and a coating. The high-adhesion super-hydrophobic protective coating process method comprises the following steps: S1, preparing magnetic nano iron oxide particles; s2, performing neodymium modification on the magnetic nano iron oxide particles to obtain ferromagnetic neodymium modified iron oxide; s3, preparing and spraying a neodymium modified iron oxide coating; s4, preparing and coating a negative charge modified polymer microsphere coating; s5, preparing and spraying a positive charge modified polymer microsphere coating; and S6, preparing and spraying a modified nano silicon dioxide super-hydrophobic coating. According to the method, neodymium-modified magnetic nanometer iron oxide serves as a first layer of the surface of a steel substrate and is sprayed and dried in a magnetic field, it is guaranteed that the neodymium-modified magnetic nanometer iron oxide is tightly adsorbed to the steel surface, a magnetic transition layer is formed, and then coatings with different charges are alternately coated through the electrostatic attraction effect; and finally, a high-adhesive-force super-hydrophobic coating is formed on the steel surface in a layer-by-layer self-assembly mode, and the problem that the adhesive force of the super-hydrophobic coating is poor is obviously solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a coating and a preparation method thereof, and in particular to a high-adhesion super-hydrophobic protective coating process method and a coating. Background Art

[0002] In the rapid development of modern industry and technology, super-hydrophobic coatings have received extensive attention and research due to their excellent waterproof, anti-fouling and self-cleaning properties. The surface of super-hydrophobic coatings usually has a rough structure at the micro-nano level and low surface energy materials, which enables water droplets to form a high contact angle and a low rolling angle on its surface, thereby achieving an excellent hydrophobic effect. This characteristic makes super-hydrophobic coatings show great application potential in many fields, such as construction, automobiles, aerospace, electronic equipment, etc.

[0003] However, when trying to apply super-hydrophobic coatings to steel surfaces, they face a series of severe challenges, one of the most critical issues being the poor adhesion of the coating to the steel surface. As a widely used structural material, the surface properties of steel have an important influence on the adhesion performance of the coating. The steel surface usually has problems such as oxide layers, impurities, and uneven roughness, which makes it extremely difficult for super-hydrophobic coatings to adhere firmly.

[0004] Traditional coating attachment methods, such as physical adsorption, chemical bonding, etc., are not ideal in the combination of super-hydrophobic coating and steel surface. Physical adsorption often depends on the van der Waals force between molecules, and this force is relatively weak, and is easily destroyed under the influence of the external environment (such as temperature change, mechanical friction, etc.), causing the coating to fall off. Although chemical bonding can provide a stronger bonding force, due to the complexity of the steel surface and the variability of chemical activity, it is difficult to form a stable and uniform chemical bond between the coating and the steel. In addition, the structure and composition characteristics of the super-hydrophobic coating itself also have an adverse effect on its adhesion on the steel surface. Super-hydrophobic coating is usually composed of low surface energy substances (such as fluorides, siloxanes, etc.) and microscopic roughness. These low surface energy substances have poor compatibility with the steel surface, and it is difficult to form a tight combination. At the same time, while providing super-hydrophobic performance, the microscopic roughness also increases the interface complexity between the coating and the substrate, making the stress distribution uneven, and easily causing the coating to peel off in the local area.

[0005] In order to solve the problem of insufficient adhesion of super-hydrophobic coatings on steel surfaces, researchers have made a lot of attempts. Some methods include pre-treatment of the steel surface, such as pickling, phosphating, sandblasting, etc., to improve surface roughness and chemical activity; optimizing the formula of the super-hydrophobic coating to add components that are more compatible with the steel surface; using a multi-layer coating structure to enhance the bonding between the coating and the substrate through an intermediate transition layer. However, although these methods have improved the adhesion of super-hydrophobic coatings to a certain extent, they still have many limitations.

[0006] Therefore, finding a simple, effective, economical method that can significantly improve the adhesion of super-hydrophobic coatings on steel surfaces has become the focus and difficulty of current research. This is not only of great significance for promoting the practical application of super-hydrophobic coatings, but also provides new ideas and directions for technological innovation and development in related fields. Summary of the invention

[0007] Purpose of the invention: The purpose of the present invention is to provide a high-adhesion super-hydrophobic protective coating process and coating.

[0008] Technical solution: The first aspect of the present invention provides a high-adhesion super-hydrophobic protective coating process method, comprising the following steps:

[0009] 1. Homemade Nano Iron Oxide:

[0010] Nano-iron oxide is prepared by hydrothermal method, sol-gel method, co-precipitation and other methods.

[0011] 2. Neodymium modified iron oxide:

[0012] Materials: NdCl3·6H2O, homemade nano-iron oxide (Fe3O4), deionized water

[0013] step:

[0014] (1) Dissolve a certain amount of NdCl3·6H2O in deionized water to prepare a neodymium chloride solution with a concentration of 0.1-0.5 mol / L.

[0015] (2) A required amount of homemade nano-iron oxide (Fe3O4) particles is added to deionized water to prepare an iron oxide solution with a concentration of 0.4-0.8 mol / L, and ultrasonic treatment is performed for a certain period of time to make it uniformly dispersed.

[0016] (3) Add the uniformly dispersed Fe3O4 solution dropwise to the NdCl3 solution, and at the same time add ammonia solution, and control the pH value of the mixed solution to between 7 and 8 by adding ammonia solution to promote the Nd 3+ Binding of ions to the Fe3O4 surface.

[0017] (4) In order to further improve the bonding strength and magnetic properties of the particles, the mixed solution was heated to 300-500°C under argon protection and stirred for 2-4 hours to promote the Nd 3+ Solid solution and lattice bonding with Fe3O4 ensure that Nd 3+ The ions are fully adsorbed on the surface of Fe3O4 particles.

[0018] (5) After the reaction is completed, the modified nano-Fe3O4 particles are separated by a centrifuge and washed with deionized water and anhydrous ethanol for multiple times to remove unreacted NdCl3 and other impurities.

[0019] (6) Drying the cleaned particles in an oven to obtain neodymium-modified nano-Fe3O4 powder.

[0020] The Fe3O4 solution and NdCl3 solution are used in a molar ratio of Nd to Fe of 0.1:1.

[0021] 3. Preparation of neodymium modified iron oxide coating:

[0022] Materials: Neodymium modified nano iron oxide powder, limonene

[0023] step:

[0024] (1) A certain amount of neodymium-modified nano-iron oxide powder is added to a limonene solvent and ultrasonically treated to uniformly disperse the powder.

[0025] (2) Add the evenly dispersed solution into the spray gun for spraying.

[0026] (3) Pre-treatment of the steel surface to be coated, including cleaning, grinding, chemical treatment and plasma treatment to improve coating adhesion.

[0027] (4) During the uniform spraying process, the pretreated steel is placed in a magnetic field to allow the neodymium-modified magnetic nano-iron oxide to be oriented and adsorbed on the steel surface.

[0028] (5) After the coating is sprayed, the coating is cured under a magnetic field to ensure uniform distribution of the modified magnetic iron oxide nanoparticles.

[0029] The dosage ratio of the neodymium-modified nano-iron oxide powder to the limonene solvent is 5-15 g: 100 mL.

[0030] 4. Preparation and coating of negatively charged modified polymer microspheres:

[0031] Materials: styrene, acrylic acid, methyl methacrylate, methacrylate trimethyl ammonium orthosulfate (MAPTAC) or other cationic monomers, sodium dodecyl sulfonate or other surfactants, ammonium persulfate or potassium persulfate or azobisisobutyronitrile (AIBN) or other initiators

[0032] step:

[0033] (1) Prepare surfactant solution.

[0034] (2) Prepare the initiator.

[0035] (3) The styrene is washed several times with NaOH solution and then washed several times with water to remove the inhibitor.

[0036] (4) Place a three-necked flask in the center of the magnetic stirrer and install a thermometer, condenser and nitrogen introduction device.

[0037] (5) Add surfactant to the three-necked flask, start stirring and passing nitrogen, and heat it in a water bath at 70-80°C. Slowly add the mixed monomers of styrene, acrylic acid and methyl methacrylate and heat for a certain period of time.

[0038] (6) Slowly add the initiator to initiate the polymerization reaction, which lasts for 4-6 hours.

[0039] (7) Stop heating, cool to room temperature, separate the solid microspheres using a centrifuge, wash with deionized water until the washing liquid is clear, and dry in a desiccator for later use.

[0040] (8) A certain amount of polymer microspheres is added to a limonene solvent and uniformly dispersed by ultrasonic treatment. The amount ratio of polymer microspheres to limonene solvent is 0.8-1.2 g: 100 mL.

[0041] (9) Using a spraying device, the negatively charged polymer microsphere coating solution is evenly sprayed onto the surface of the substrate on which the magnetic particle coating has been sprayed.

[0042] (10) Dry at room temperature or in an oven.

[0043] The dosage of the surfactant, initiator and mixed monomer is as follows: the dosage of the surfactant is 0.05-0.1 g / 100 mL of deionized water, the dosage of the initiator is 0.2-0.6 g / 2 mL of deionized water, and the dosage of the mixed monomer is 10.4-16.4 g.

[0044] The mixed monomer consists of styrene, acrylic acid and methyl methacrylate, and the usage is: 10-15g styrene, 0.2-0.7g acrylic acid and 0.2-0.7g methyl methacrylate.

[0045] 5. Preparation of positively charged polymer microspheres:

[0046] Materials: Styrene (St), methacrylate trimethyl ammonium sulfate (MAPTAC) or other cationic monomers, sodium dodecyl sulfonate or other surfactants, ammonium persulfate or potassium persulfate or azobisisobutyronitrile (AIBN) or other initiators, deionized water (DI water), pH adjuster (NaOH or HCl)

[0047] step:

[0048] (1) Prepare surfactant solution.

[0049] (2) Prepare the initiator.

[0050] (3) The styrene is washed several times with NaOH solution and then washed several times with water to remove the inhibitor.

[0051] (4) Place a three-necked flask in the center of the magnetic stirrer and install a thermometer, condenser and nitrogen introduction device.

[0052] (5) Add the surfactant solution to the three-necked flask and start stirring. At the same time, fill it with sufficient nitrogen to prevent air from affecting the polymerization reaction. Set the water bath temperature to 70-80°C; after the water bath temperature stabilizes, slowly add a certain amount of mixed monomer (styrene + methacrylate trimethyl orthosulfate amino ester) to the reaction solution, continue stirring, and heat for a certain period of time.

[0053] (6) Add initiator to initiate polymerization reaction, and the reaction lasts for 4-6 hours. During this period, the temperature and stirring rate are kept stable, and nitrogen is continuously introduced during the reaction to prevent oxygen from entering.

[0054] (7) Stop heating, cool to room temperature, and separate the solid microspheres using a centrifuge. Wash the microspheres repeatedly with deionized water until the washing liquid is clear. Dry the washed microspheres in a vacuum dryer.

[0055] (8) Finally, the positively charged polymer microspheres are uniformly dispersed in the organic solvent by ultrasonic treatment, and the dosage ratio of the polymer microspheres to the limonene solvent is 0.8-1.2 g: 100 mL.

[0056] (9) Coating spraying: Use a spraying device to evenly spray the positively charged polymer microsphere coating solution onto the surface of the substrate that has been sprayed with the negatively charged polymer microsphere coating.

[0057] The dosage of the surfactant, initiator and mixed monomer is: 0.1-0.5 g of surfactant / 100 mL of deionized water, 0.1-0.3 g of initiator / 2 mL of deionized water, and 10.8-16.2 g of mixed monomer.

[0058] (10) Dry at room temperature or in an oven.

[0059] The mixed monomer is composed of styrene and methacrylate trimethyl orthosulfate amino, and the dosage is: 10-15g styrene and 0.8-1.2g methacrylate trimethyl orthosulfate amino.

[0060] 6. Preparation of modified nano-silica super-hydrophobic coating:

[0061] Materials: hydrophilic nano-SiO2 powder, acetic acid, ethanol, perfluorotriethoxysilane, dimethoxysilane, ethyl orthosilicate

[0062] step:

[0063] (1) A certain amount of hydrophilic nano-SiO2 powder is added to an ethanol solution containing acetic acid and magnetically stirred to disperse it evenly.

[0064] (2) Add a certain amount of perfluorotriethoxysilane, dimethoxysilane and ethyl orthosilicate to the above solution system, perform magnetic stirring to make the mixture evenly mixed, and obtain a milky white suspension, which is then centrifuged and separated. The separated solid substance is dried to obtain a modified super-hydrophobic nano-SiO2 powder, and then ground and debonded with zirconium beads to obtain a super-hydrophobic nano-SiO2 powder.

[0065] (3) A certain amount of super-hydrophobic nano-SiO2 powder is added to the limonene solvent and ultrasonically treated to disperse it evenly. The amount ratio of the polymer microspheres to the limonene solvent is 1N10g:100mL.

[0066] (4) Then, an equal amount of SEPS super-hydrophobic special adhesive as the nano-SiO2 powder is added, and mechanical stirring is performed until the adhesive is completely dissolved to obtain a coating solution.

[0067] (5) Using a spraying device, the modified nano-silica super-hydrophobic coating is evenly sprayed on the surface of the above-mentioned film layer, and solidified in air to obtain a super-hydrophobic coating.

[0068] The mass ratio of the SiO2 powder, perfluorotriethoxysilane, dimethoxysilane and ethyl orthosilicate is 6-10:3-7:8-12:8N12.

[0069] Another aspect of the present invention provides a coating prepared by a high-adhesion super-hydrophobic protective coating process method.

[0070] The method of the present invention uses neodymium-modified magnetic nano-iron oxide as the first layer on the surface of the steel substrate, which is tightly adsorbed on the steel surface to form a magnetic transition layer, thereby significantly improving the adhesion of the super-hydrophobic coating on the steel surface. Afterwards, a negatively charged polymer microsphere film layer is coated on the surface of the negatively charged magnetic nanoparticles, and the binding force between the film layers is enhanced by electrostatic attraction and van der Waals force. Then, a layer of positively charged polymer microsphere film layer is coated, and finally a negatively charged modified nano-silicon dioxide super-hydrophobic film layer is coated on the surface, and a continuous multilayer film coating is constructed by alternately coating the film layers with opposite charges. It not only significantly improves the adhesion of the coating on the surface of steel, but also gives it a super-hydrophobic function, solving the problems of low adhesion, easy falling off and poor protective performance of the super-hydrophobic coating.

[0071] Compared with the prior art, the present invention has the following beneficial effects:

[0072] 1. Neodymium modified iron oxide has good magnetic properties. When used on the surface of steel substrates, it can not only improve the adhesion of the coating, but also enhance the mechanical strength and corrosion resistance of the coating.

[0073] 2. By alternately coating layers of opposite charges and giving different functions to the bottom and top layers, high adhesion and super hydrophobicity of the coating can be achieved.

[0074] 3. Applying polymer microspheres modified with different charges between membrane layers enhances the bonding force between membrane layers through electrostatic attraction and full utilization of van der Waals forces, thereby improving the stability and durability of the superhydrophobic coating and broadening its application range.

[0075] 4. Limonene is a natural ingredient found in many fruits and spices. Using it as a solvent can significantly improve the environmental performance of coatings. DETAILED DESCRIPTION

[0076] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be further described below.

[0077] Example 1

[0078] 1. Preparation of nano iron oxide by coprecipitation method:

[0079] Materials: ferric chloride hexahydrate (FeCl3·6H2O), ferrous sulfate heptahydrate (FeSO4·7H2O), ammonia water, distilled water, nitrogen

[0080] step:

[0081] (1) Add distilled water equivalent to 3 / 5 of the reactor volume into the reactor and fill it with nitrogen to remove air.

[0082] (2) Add ferric chloride hexahydrate (FeCl3·6H2O) and ferrous sulfate heptahydrate (FeSO4·7H2O) into a reaction kettle in a mass ratio of 2:1 and mix to obtain a solution.

[0083] (3) Adding 1 / 10 volume of aqueous ammonia to the mixed solution, heating to 50° C., and cooling to obtain an iron oxide precipitate.

[0084] (4) The obtained iron oxide nanoparticles were washed and separated six times.

[0085] (5) Finally, the iron oxide nanoparticles are dried in a vacuum drying oven to obtain nano magnetic iron oxide particles.

[0086] 2. Neodymium modified iron oxide:

[0087] Materials: NdCl3·6H2O, homemade nano-iron oxide (Fe3O4), deionized water

[0088] step:

[0089] (1) Dissolve a certain amount of NdCl3·6H2O in deionized water to prepare a neodymium chloride solution with a concentration of 0.3 mol / L.

[0090] (2) A required amount of homemade nano-iron oxide (Fe3O4) particles was added into deionized water to prepare an iron oxide solution with a concentration of 0.6 mol / L, and ultrasonic treatment was performed for 30 min to make it evenly dispersed.

[0091] (3) Add the uniformly dispersed Fe3O4 solution dropwise into the NdCl3 solution, and add an appropriate amount of ammonia water to control the pH value of the mixed solution between 7 and 8 to promote the Nd 3+ Binding of ions to the Fe3O4 surface.

[0092] (4) In order to further improve the bonding strength and magnetic properties of the particles, the mixed solution was heated to 400 °C under argon protection and stirred for 3 h to promote the reaction of Nd 3+ Solid solution and lattice bonding with Fe3O4 ensure that Nd 3+ The ions are fully adsorbed on the surface of Fe3O4 particles.

[0093] (5) After the reaction is completed, the modified nano-Fe3O4 particles are separated by a centrifuge (4000 rpm, 10 min) and washed with deionized water and anhydrous ethanol for multiple times to remove unreacted NdCl3 and other impurities.

[0094] (6) The cleaned particles were dried in an oven at 60°C for 12 h to obtain neodymium-modified nano-Fe3O4 powder.

[0095] 3. Preparation of neodymium modified iron oxide coating:

[0096] Materials: Neodymium modified nano iron oxide powder, limonene

[0097] step:

[0098] (1) Add 10 g of neodymium-modified nano-iron oxide powder into 100 mL of limonene and treat it with ultrasound for 30 min to make it evenly dispersed.

[0099] (2) Add the evenly dispersed solution into the spray gun for spraying.

[0100] (3) Pre-treatment of the steel surface to be coated, including cleaning, grinding, chemical treatment and plasma treatment to improve coating adhesion.

[0101] (4) During the uniform spraying process, the pretreated steel is placed in a magnetic field with a magnetic field strength of 8A / m, so that the neodymium-modified magnetic nano-iron oxide is oriented and adsorbed on the surface of the steel.

[0102] (5) After the coating is sprayed, the coating is cured under a magnetic field strength of 8 A / m to ensure uniform distribution of the modified magnetic iron oxide nanoparticles.

[0103] 4. Preparation and coating of negatively charged modified polymer microspheres:

[0104] Materials: styrene, acrylic acid, methyl methacrylate, sodium dodecyl sulfonate, ammonium persulfate, deionized water, NaOH

[0105] step:

[0106] (1) Weigh 0.05 g of sodium dodecyl sulfate and dissolve it in 100 mL of deionized water as a surfactant.

[0107] (2) Dissolve 0.45 g of ammonium persulfate in 2 mL of deionized water to prepare the initiator.

[0108] (3) Styrene was washed three times with 1 mol / L NaOH and then washed three times with deionized water to remove the inhibitor.

[0109] (4) Place a three-necked flask in the center of the magnetic stirrer and install a thermometer, condenser and nitrogen introduction device.

[0110] (5) Add sodium dodecyl sulfate solution to a three-necked flask, start stirring and passing nitrogen, and heat in a water bath at 75°C. Slowly add mixed monomers (12 g styrene + 0.5 g acrylic acid + 0.5 g methyl methacrylate) and heat for 0.5 h.

[0111] (6) Slowly add ammonium persulfate solution to initiate the polymerization reaction, and the reaction lasts for 5 hours.

[0112] (7) Stop heating, cool to room temperature, filter the emulsion three times, separate the solid microspheres using a centrifuge (8000 rpm, 10 min), wash with deionized water until the washing liquid is clear, and dry in a desiccator.

[0113] (8) 1 g of negatively charged polymer microspheres was added to 100 mL of limonene solvent and dispersed uniformly by ultrasonic treatment.

[0114] (9) Using a spraying device, the negatively charged polymer microsphere coating solution is evenly sprayed onto the surface of the substrate on which the magnetic particle coating has been sprayed.

[0115] (10) Dry at room temperature or in an oven.

[0116] 5. Preparation of positively charged polymer microspheres:

[0117] Materials: styrene (St), methacrylate trimethyl orthosulfate amino ester (MAPTAC) monomer, sodium dodecyl sulfonate, ammonium persulfate, deionized water, NaOH

[0118] step:

[0119] (1) Dissolve 0.05 g of sodium dodecyl sulfate in 100 mL of deionized water to prepare a surfactant solution.

[0120] (2) Weigh 0.45 g of ammonium persulfate and dissolve it in 2 mL of deionized water to prepare an initiator.

[0121] (3) Styrene was washed three times with 1 mol / L NaOH and then washed three times with deionized water to remove the inhibitor.

[0122] (4) Place a three-necked flask in the center of the magnetic stirrer and install a thermometer, condenser and nitrogen introduction device.

[0123] (5) Add sodium dodecylbenzene sulfonate solution into a three-necked flask and start stirring. At the same time, fill with sufficient nitrogen to prevent air from affecting the polymerization reaction. Set the water bath temperature to 75°C; after the water bath temperature stabilizes, slowly add a certain amount of mixed monomers (12g styrene + 1g trimethylol orthosulfate methacrylate) into the reaction solution, continue stirring, and heat for 0.5h.

[0124] (6) Add initiator to initiate polymerization reaction, and the reaction lasts for 5 hours. During this period, the temperature and stirring rate are kept stable, and nitrogen is continuously introduced during the reaction to prevent oxygen from entering.

[0125] (7) Stop heating, cool to room temperature, and centrifuge at 8000 rpm for 10 min to separate solid microspheres. Wash the microspheres repeatedly with deionized water until the washing liquid is clear. Dry the washed microspheres in a vacuum dryer.

[0126] (8) 1 g of the positively charged polymer microspheres was added to 100 mL of limonene solvent and uniformly dispersed by ultrasonic treatment to obtain a positively charged polymer microsphere coating.

[0127] (9) Coating spraying: Use a spraying device to evenly spray the positively charged polymer microsphere coating solution onto the surface of the substrate that has been sprayed with the negatively charged polymer microsphere coating.

[0128] (10) Dry at room temperature or in an oven.

[0129] 6. Preparation of modified nano-silica super-hydrophobic coating:

[0130] Materials: hydrophilic nano-SiO2 powder, acetic acid, ethanol, perfluorotriethoxysilane, dimethoxysilane, ethyl orthosilicate

[0131] step:

[0132] (1) 8 g of hydrophilic nano-SiO2 powder was added to 100 mL of ethanol solution containing 5% acetic acid by mass, and magnetically stirred at 1000 rpm for 30 min.

[0133] (2) Add 5 g of perfluorotriethoxysilane, 10 g of dimethoxysilane and 10 g of ethyl orthosilicate to the above solution system, stir magnetically at a speed of 500 rpm for 3 h, mix evenly to obtain a milky white suspension, and then centrifuge for 30 min. After drying, the modified super-hydrophobic nano-SiO2 powder is obtained, and then ground and debonded with zirconium beads to obtain super-hydrophobic nano-SiO2 powder.

[0134] (3) Add 5 g of super-hydrophobic nano-SiO2 powder into 100 mL of limonene solvent and ultrasonically treat for 10 min to achieve uniform dispersion.

[0135] (4) Then, an equal amount of SEPS super-hydrophobic special adhesive as that of SiO2 powder was added and mechanically stirred for 45 min until the adhesive was completely dissolved to obtain a coating solution.

[0136] (5) Using a spraying device, the modified nano-silica super-hydrophobic coating is evenly sprayed on the surface of the above-mentioned film layer, and cured in air for 2 hours to obtain a super-hydrophobic coating.

[0137] Example 2

[0138] 1. Preparation of nano iron oxide by hydrothermal method:

[0139] Materials: ferric chloride (FeCl3·6H2O), sodium hydroxide (NaOH), deionized water, anhydrous ethanol

[0140] step:

[0141] (1) Dissolve 20 g of FeCl3·6H2O in 100 mL of deionized water and stir on a magnetic stirrer until completely dissolved to obtain an orange-yellow solution.

[0142] (2) While stirring continuously, slowly add sodium hydroxide solution and monitor the pH value of the solution in real time using a pH meter until the pH value of the solution reaches 10.

[0143] (3) The solution with adjusted pH value was transferred to a high-pressure reactor, the filling degree was controlled at about 70%, the reactor was sealed, and it was placed in an oven, the temperature was set to 180° C., and a hydrothermal reaction was carried out for 12 h.

[0144] (4) After the reaction is completed, the autoclave is cooled naturally to room temperature. The autoclave is opened, the product is poured out, and washed with deionized water and anhydrous ethanol three times respectively.

[0145] (5) The washed product was placed in an oven and dried at 80° C. for 10 h to obtain nano iron oxide powder.

[0146] 2. Neodymium modified iron oxide:

[0147] Materials: NdCl3·6H2O, homemade nano-iron oxide (Fe3O4), deionized water

[0148] step:

[0149] (1) Dissolve a certain amount of NdCl3·6H2O in deionized water to prepare a neodymium chloride solution with a concentration of 0.3 mol / L.

[0150] (2) A required amount of homemade nano-iron oxide (Fe3O4) particles was added into deionized water to prepare an iron oxide solution with a concentration of 0.6 mol / L, and ultrasonic treatment was performed for 30 min to make it evenly dispersed.

[0151] (3) Add the uniformly dispersed Fe3O4 solution dropwise into the NdCl3 solution, with the molar ratio of Nd to Fe being 0.1:1, and add an appropriate amount of ammonia water to adjust the pH value of the mixed solution to 7.5 to promote the Nd 3+ Binding of ions to the Fe3O4 surface.

[0152] (4) In order to further improve the bonding strength and magnetic properties of the particles, the mixed solution was heated to 400 °C under argon protection and stirred for 3 h to promote the reaction of Nd 3+Solid solution and lattice bonding with Fe3O4 ensure that Nd 3+ The ions are fully adsorbed on the surface of Fe3O4 particles.

[0153] (5) After the reaction is completed, the modified nano-Fe3O4 particles are separated by a centrifuge (4000 rpm, 10 min) and washed with deionized water and anhydrous ethanol for multiple times to remove unreacted NdCl3 and other impurities.

[0154] (6) The cleaned particles were dried in an oven at 60°C for 12 h to obtain neodymium-modified nano-Fe3O4 powder.

[0155] 3. Preparation of neodymium modified iron oxide coating:

[0156] Materials: Neodymium modified nano iron oxide powder, limonene

[0157] step:

[0158] (1) Add 10 g of neodymium-modified nano-iron oxide powder into 100 mL of limonene and treat it with ultrasound for 30 min to make it evenly dispersed.

[0159] (2) Add the evenly dispersed solution into the spray gun for spraying.

[0160] (3) Pre-treatment of the steel surface to be coated, including cleaning, grinding, chemical treatment and plasma treatment to improve coating adhesion.

[0161] (4) During the uniform spraying process, the pretreated steel is placed in a magnetic field with a magnetic field strength of 8A / m, so that the neodymium-modified magnetic nano-iron oxide is oriented and adsorbed on the surface of the steel.

[0162] (5) After the coating is sprayed, the coating is cured under a magnetic field strength of 8 A / m to ensure uniform distribution of the modified magnetic iron oxide nanoparticles.

[0163] 4. Preparation and coating of negatively charged modified polymer microspheres:

[0164] Materials: styrene, acrylic acid, methyl methacrylate, sodium dodecyl sulfonate, ammonium persulfate, deionized water, NaOH

[0165] step:

[0166] (1) Weigh 0.05 g of sodium dodecyl sulfate and dissolve it in 100 mL of deionized water as an emulsifier.

[0167] (2) Dissolve 0.45 g of ammonium persulfate in 2 mL of deionized water to prepare the initiator.

[0168] (3) Styrene was washed three times with 1 mol / L NaOH and then washed three times with deionized water to remove the inhibitor.

[0169] (4) Place a three-necked flask in the center of the magnetic stirrer and install a thermometer, condenser and nitrogen introduction device.

[0170] (5) Add sodium dodecyl sulfate solution to a three-necked flask, start stirring and passing nitrogen, and heat in a water bath at 75°C. Slowly add mixed monomers (12 g styrene + 0.5 g acrylic acid + 0.5 g methyl methacrylate) and heat for 0.5 h.

[0171] (6) Slowly add ammonium persulfate solution to initiate the polymerization reaction, and the reaction lasts for 5 hours.

[0172] (7) Stop heating, cool to room temperature, filter the emulsion three times, separate the solid microspheres using a centrifuge (8000 rpm, 10 min), wash with deionized water until the washing liquid is clear, and dry in a desiccator.

[0173] (8) 1 g of negatively charged polymer microspheres was added to 100 mL of limonene solvent and uniformly dispersed by ultrasonic treatment to obtain a negatively charged polymer microsphere coating.

[0174] (9) Using a spraying device, the negatively charged polymer microsphere coating solution is evenly sprayed onto the surface of the substrate on which the magnetic particle coating has been sprayed.

[0175] (10) Dry at room temperature or in an oven.

[0176] 5. Preparation of positively charged polymer microspheres:

[0177] Materials: styrene (St), methacrylate trimethyl orthosulfate amino ester (MAPTAC) monomer, sodium dodecyl sulfonate, ammonium persulfate, deionized water, NaOH

[0178] step:

[0179] (1) Dissolve 0.05 g of sodium dodecyl sulfate in 100 mL of deionized water to prepare a surfactant solution.

[0180] (2) Weigh 0.45 g of ammonium persulfate and dissolve it in 2 mL of deionized water to prepare an initiator.

[0181] (3) Styrene was washed three times with 1 mol / L NaOH and then washed three times with deionized water to remove the inhibitor.

[0182] (4) Place a three-necked flask in the center of the magnetic stirrer and install a thermometer, condenser and nitrogen introduction device.

[0183] (5) Add sodium dodecylbenzene sulfonate solution into a three-necked flask and start stirring. At the same time, fill with sufficient nitrogen to prevent air from affecting the polymerization reaction. Set the water bath temperature to 75°C; after the water bath temperature stabilizes, slowly add a certain amount of mixed monomers (12g styrene + 1g trimethylol orthosulfate methacrylate) into the reaction solution, continue stirring, and heat for 0.5h.

[0184] (6) Add initiator to initiate polymerization reaction, and the reaction lasts for 5 hours. During this period, the temperature and stirring rate are kept stable, and nitrogen is continuously introduced during the reaction to prevent oxygen from entering.

[0185] (7) Stop heating, cool to room temperature, and centrifuge at 8000 rpm for 10 min to separate solid microspheres. Wash the microspheres repeatedly with deionized water until the washing liquid is clear. Dry the washed microspheres in a vacuum dryer.

[0186] (8) 1 g of the positively charged polymer microspheres was added to 100 mL of limonene solvent and uniformly dispersed by ultrasonic treatment to obtain a positively charged polymer microsphere coating.

[0187] (9) Coating spraying: Use a spraying device to evenly spray the positively charged polymer microsphere coating solution onto the surface of the substrate that has been sprayed with the negatively charged polymer microsphere coating.

[0188] (10) Dry at room temperature or in an oven.

[0189] 6. Preparation of modified nano-silica super-hydrophobic coating:

[0190] Materials: hydrophilic nano-SiO2 powder, acetic acid, ethanol, perfluorotriethoxysilane, dimethoxysilane, ethyl orthosilicate

[0191] step:

[0192] (1) 8 g of hydrophilic nano-SiO2 powder was added to 100 mL of ethanol solution containing 5% acetic acid by mass, and magnetically stirred at 1000 rpm for 30 min.

[0193] (2) Add 5 g of perfluorotriethoxysilane, 10 g of dimethoxysilane and 10 g of ethyl orthosilicate to the above solution system, stir magnetically at a speed of 500 rpm for 3 h, mix evenly to obtain a milky white suspension, and then centrifuge for 30 min. After drying, the modified super-hydrophobic nano-SiO2 powder is obtained, and then ground and debonded with zirconium beads to obtain super-hydrophobic nano-SiO2 powder.

[0194] (3) Add 5 g of super-hydrophobic nano-SiO2 powder into 100 mL of limonene solvent and ultrasonically treat for 10 min to achieve uniform dispersion.

[0195] (4) Then, an equal amount of SEPS super-hydrophobic special adhesive as that of SiO2 powder was added and mechanically stirred for 45 min until the adhesive was completely dissolved to obtain a coating solution.

[0196] (5) Using a spraying device, the modified nano-silica super-hydrophobic coating is evenly sprayed on the surface of the above-mentioned film layer, and cured in air for 2 hours to obtain a super-hydrophobic coating.

[0197] Comparative Example 1

[0198] 1. Preparation of nano iron oxide by coprecipitation method:

[0199] Materials: ferric chloride hexahydrate (FeCl3·6H2O), ferrous sulfate heptahydrate (FeSO4·7H2O), ammonia water, distilled water, nitrogen

[0200] step:

[0201] (1) Add distilled water equivalent to 3 / 5 of the reactor volume into the reactor and fill it with nitrogen to remove air.

[0202] (2) Add ferric chloride hexahydrate (FeCl3·6H2O) and ferrous sulfate heptahydrate (FeSO4·7H2O) into a reaction kettle in a mass ratio of 2:1 and mix to obtain a solution.

[0203] (3) Adding 1 / 10 volume of aqueous ammonia to the mixed solution, heating to 50° C., and cooling to obtain an iron oxide precipitate.

[0204] (4) The obtained iron oxide nanoparticles were washed and separated six times.

[0205] (5) Finally, the iron oxide nanoparticles are dried in a vacuum drying oven to obtain nano magnetic iron oxide particles.

[0206] 2. Preparation of Nano-Iron Oxide Coating:

[0207] Materials: Nano iron oxide powder, limonene

[0208] step:

[0209] (1) Add 10 g of nano iron oxide powder into 100 mL of limonene solvent and treat with ultrasound for 30 min to make it evenly dispersed.

[0210] (2) Add the evenly dispersed solution into the spray gun for spraying.

[0211] (3) Pre-treatment of the steel surface to be coated, including cleaning, grinding, chemical treatment and plasma treatment to improve coating adhesion.

[0212] (4) During the uniform spraying process, the pretreated steel is placed in a magnetic field with a magnetic field strength of 8A / m, so that the neodymium-modified magnetic nano-iron oxide is oriented and adsorbed on the surface of the steel.

[0213] (5) After the coating is sprayed, the coating is cured under a magnetic field strength of 8 A / m to ensure uniform distribution of the modified magnetic iron oxide nanoparticles.

[0214] 3. Preparation and coating of negatively charged modified polymer microspheres:

[0215] Materials: styrene, acrylic acid, methyl methacrylate, sodium dodecyl sulfonate, ammonium persulfate, deionized water, NaOH

[0216] step:

[0217] (1) Weigh 0.05 g of sodium dodecyl sulfate and dissolve it in 100 mL of deionized water as an emulsifier.

[0218] (2) Dissolve 0.45 g of ammonium persulfate in 2 mL of deionized water to prepare the initiator.

[0219] (3) Styrene was washed three times with 1 mol / L NaOH and then washed three times with deionized water to remove the inhibitor.

[0220] (4) Place a three-necked flask in the center of the magnetic stirrer and install a thermometer, condenser and nitrogen introduction device.

[0221] (5) Add sodium dodecyl sulfate solution to a three-necked flask, start stirring and passing nitrogen, and heat in a water bath at 75°C. Slowly add mixed monomers (12 g styrene + 0.5 g acrylic acid + 0.5 g methyl methacrylate) and heat for 0.5 h.

[0222] (6) Slowly add ammonium persulfate solution to initiate the polymerization reaction, and the reaction lasts for 5 hours.

[0223] (7) Stop heating, cool to room temperature, filter the emulsion three times, separate the solid microspheres using a centrifuge (8000 rpm, 10 min), wash with deionized water until the washing liquid is clear, and dry in a desiccator.

[0224] (8) 1 g of negatively charged polymer microspheres was added to 100 mL of limonene solvent and dispersed uniformly by ultrasonic treatment.

[0225] (9) Using a spraying device, the negatively charged polymer microsphere coating solution is evenly sprayed onto the surface of the substrate on which the magnetic particle coating has been sprayed.

[0226] (10) Dry at room temperature or in an oven.

[0227] 4. Preparation of positively charged polymer microspheres:

[0228] Materials: styrene (St), methacrylate trimethyl orthosulfate amino ester (MAPTAC) monomer, sodium dodecyl sulfonate, ammonium persulfate, deionized water, NaOH

[0229] step:

[0230] (1) Dissolve 0.05 g of sodium dodecyl sulfate in 100 mL of deionized water to prepare a surfactant solution.

[0231] (2) Weigh 0.45 g of ammonium persulfate and dissolve it in 2 mL of deionized water to prepare an initiator.

[0232] (3) Styrene was washed three times with 1 mol / L NaOH and then washed three times with deionized water to remove the inhibitor.

[0233] (4) Place a three-necked flask in the center of the magnetic stirrer and install a thermometer, condenser and nitrogen introduction device.

[0234] (5) Add sodium dodecylbenzene sulfonate solution into a three-necked flask and start stirring. At the same time, fill with sufficient nitrogen to prevent air from affecting the polymerization reaction. Set the water bath temperature to 75°C; after the water bath temperature stabilizes, slowly add a certain amount of mixed monomers (12g styrene + 1g trimethylol orthosulfate methacrylate) into the reaction solution, continue stirring, and heat for 0.5h.

[0235] (6) Add initiator to initiate polymerization reaction, and the reaction lasts for 5 hours. During this period, the temperature and stirring rate are kept stable, and nitrogen is continuously introduced during the reaction to prevent oxygen from entering.

[0236] (7) Stop heating, cool to room temperature, and centrifuge at 8000 rpm for 10 min to separate solid microspheres. Wash the microspheres repeatedly with deionized water until the washing liquid is clear. Dry the washed microspheres in a vacuum dryer.

[0237] (8) 1 g of the positively charged polymer microspheres was added to 100 mL of limonene solvent and uniformly dispersed by ultrasonic treatment to obtain a positively charged polymer microsphere coating.

[0238] (9) Coating spraying: Use a spraying device to evenly spray the positively charged polymer microsphere coating solution onto the surface of the substrate that has been sprayed with the negatively charged polymer microsphere coating.

[0239] (10) Dry at room temperature or in an oven.

[0240] 5. Preparation of modified nano-silica super-hydrophobic coating:

[0241] Materials: hydrophilic nano-SiO2 powder, acetic acid, ethanol, perfluorotriethoxysilane, dimethoxysilane, ethyl orthosilicate

[0242] step:

[0243] (1) 8 g of hydrophilic nano-SiO2 powder was added to 100 mL of ethanol solution containing 5% acetic acid by mass, and magnetically stirred at 1000 rpm for 30 min.

[0244] (2) Add 5 g of perfluorotriethoxysilane, 10 g of dimethoxysilane and 10 g of ethyl orthosilicate to the above solution system, stir magnetically at a speed of 500 rpm for 3 h, mix evenly to obtain a milky white suspension, and then centrifuge for 30 min. After drying, the modified super-hydrophobic nano-SiO2 powder is obtained, and then ground and debonded with zirconium beads to obtain super-hydrophobic nano-SiO2 powder.

[0245] (3) Add 5 g of super-hydrophobic nano-SiO2 powder into 100 mL of limonene solvent and ultrasonically treat for 10 min to achieve uniform dispersion.

[0246] (4) Then, an equal amount of SEPS super-hydrophobic special adhesive as that of SiO2 powder was added and mechanically stirred for 45 min until the adhesive was completely dissolved to obtain a coating solution.

[0247] (5) Using a spraying device, the modified nano-silica super-hydrophobic coating is evenly sprayed on the surface of the above-mentioned film layer, and cured in air for 2 hours to obtain a super-hydrophobic coating.

[0248] Comparative Example 2

[0249] Compared with Example 1, the modified nano-silica super-hydrophobic coating is not applied at the end, and other technical solutions are the same as Example 1.

[0250] Table 1

[0251] Performance Indicators Example 1 Example 2 Comparative Example 1 Comparative Example 2 Adhesion Level 1 Level 1 Level 3 Level 1 Contact Angle 158° 158° 158° 101°

[0252] It can be seen that the present invention uses neodymium-modified magnetic nano-iron oxide as the first layer on the surface of the steel substrate, which can significantly improve the adhesion of the coating on the steel surface. At the same time, the coating constructed by layer-by-layer self-assembly has a strong superhydrophobic ability.

[0253] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any technician in the relevant technical field, without departing from the scope of the technical solution of the present invention, makes any form of equivalent replacement or modification to the technical solution and technical content disclosed in the present invention, which does not depart from the content of the technical solution of the present invention and still falls within the protection scope of the present invention.

Claims

1. A process for producing a high-adhesion super-hydrophobic protective coating, characterized in that: The steps include: S1, preparing magnetic nano iron oxide particles; S2, modifying the magnetic nano iron oxide particles with neodymium to obtain strongly magnetic neodymium-modified iron oxide; S3, preparation and spraying of neodymium modified iron oxide coating; S4, preparation and coating of negatively charged modified polymer microsphere coating; S5, preparation and spraying of positively charged modified polymer microsphere coating; S6. Preparation and spraying of modified nano-silica super-hydrophobic coating.

2. The process for producing a high-adhesion super-hydrophobic protective coating according to claim 1, wherein: The preparation method of step S1: preparing nano iron oxide by hydrothermal method, sol-gel method or co-precipitation method.

3. The process for producing a high-adhesion super-hydrophobic protective coating according to claim 1, wherein: The preparation method of step S2: (1) dissolving a certain amount of NdCl3·6H2O in deionized water to prepare a neodymium chloride solution with a concentration of 0.1-0.5 mol / L; (2) adding a required amount of nano iron oxide particles into deionized water to prepare an iron oxide solution with a concentration of 0.4-0.8 mol / L, and ultrasonically treating the solution to uniformly disperse the solution; (3) adding the uniformly dispersed Fe3O4 solution to the NdCl3 solution, and simultaneously adding an aqueous ammonia solution dropwise to control the pH value of the mixed solution to be between 7 and 8; (4) The mixed solution is heated to 300-500° C. under inert gas protection and stirred for reaction for 2-4 hours; (5) After the reaction is completed, the modified nano-Fe3O4 particles are separated and washed to remove unreacted NdC13 and other impurities; (6) drying to obtain neodymium-modified nano iron oxide powder; The Fe3O4 solution and NdCl3 solution are used in a molar ratio of Nd to Fe of 0.1:

1.

4. The process for producing a high-adhesion super-hydrophobic protective coating according to claim 3, wherein: The preparation method of step S3: (1) adding neodymium-modified nano-iron oxide powder to limonene, ultrasonically treating the mixture, and uniformly dispersing the mixture; (2) adding the uniformly dispersed solution into a spray gun for spraying; (3) Pre-treating the surface of the steel to be coated; (4) During the uniform spraying process, the pretreated steel is placed in a magnetic field to allow the neodymium-modified magnetic nano-iron oxide to be oriented and adsorbed on the surface of the steel; (5) After the coating is sprayed, the coating is cured under a magnetic field to ensure uniform distribution of the modified magnetic iron oxide nanoparticles. The dosage ratio of the neodymium modified nano iron oxide powder to the limonene solvent is 5-15 g: 100 mL.

5. The process for producing a high-adhesion super-hydrophobic protective coating according to claim 3, wherein: The preparation method of step S4: (1) preparing a surfactant solution: adding a surfactant into deionized water; (2) preparing the initiator: adding the initiator into deionized water; (3) washing the styrene with a NaOH solution for multiple times and then washing with water for multiple times to remove the inhibitor; (4) Place the container at the center of the magnetic stirrer and install a thermometer, condenser and nitrogen inlet device. (5) Add surfactant to the container, start stirring and pass nitrogen, place in a water bath at 70-80°C and heat, add the mixed monomer consisting of cationic monomers, and heat for a certain period of time; (6) Slowly add the initiator to initiate the polymerization reaction, and the reaction lasts for 4-6 hours; (7) stopping heating, cooling to room temperature, separating the solid microspheres, washing, and drying; (8) A certain amount of polymer microspheres are added to a limonene solvent and uniformly dispersed by ultrasonic treatment. The ratio of polymer microspheres to limonene solvent is: 0.8~1.2g:100mL; (9) using a spraying device to evenly spray the negatively charged polymer microsphere coating solution onto the surface of the substrate on which the magnetic particle coating has been sprayed; (10) Dry at room temperature or in an oven. The dosage of the surfactant, initiator and mixed monomer is as follows: the dosage of the surfactant is 0.05-0.1 g / 100 mL of deionized water, the dosage of the initiator is 0.2-0.6 g / 2 mL of deionized water, and the dosage of the mixed monomer is 10.4-16.4 g.

6. The process for producing a high-adhesion super-hydrophobic protective coating according to claim 5, characterized in that: The surfactant is selected from sodium dodecyl sulfonate; the initiator is selected from ammonium persulfate, potassium persulfate or azobisisobutyronitrile; the mixed monomer consists of styrene, acrylic acid and methyl methacrylate, and the dosage is: 10-15g styrene, 0.2-0.7g acrylic acid, and 0.2-0.7g methyl methacrylate.

7. The process for producing a high-adhesion super-hydrophobic protective coating according to claim 1, characterized in that: The preparation method of step S5: (1) preparing a surfactant solution: dissolving a surfactant in deionized water to obtain; (2) preparing the initiator: dissolving the initiator in deionized water to obtain; (3) washing styrene with a NaOH solution and washing with water to remove the inhibitor; (4) Place the stirring container at the center of the magnetic stirrer and install a thermometer, condenser and nitrogen introduction device; (5) adding the surfactant solution into the container, stirring, filling with sufficient nitrogen, and setting the water bath temperature to 70-80° C.; after the temperature of the water bath stabilizes, adding the mixed monomer composed of the cationic monomer into the reaction solution, stirring, and heating; (6) Add initiator, and continue the reaction for 4-6 hours, while nitrogen is continuously introduced during the reaction; (7) stopping heating, cooling to room temperature, separating the solid microspheres, and drying the washed microspheres; (8) The positively charged polymer microspheres are uniformly dispersed in an organic solvent, and the amount ratio of the polymer microspheres to the limonene solvent is: 0.8~1.2g:100mL; (9) spraying the positively charged polymer microsphere coating solution onto the surface of the substrate sprayed with the negatively charged polymer microsphere coating, The dosage of the surfactant, initiator and mixed monomer is: 0.1-0.5 g of surfactant / 100 mL of deionized water, 0.1-0.3 g of initiator / 2 mL of deionized water, and 10.8-16.2 g of mixed monomer.

8. The process for producing a high-adhesion super-hydrophobic protective coating according to claim 7, wherein: The surfactant is selected from sodium dodecyl sulfonate; the initiator is selected from ammonium persulfate, potassium persulfate or azobisisobutyronitrile; the mixed monomer is composed of styrene + methacrylate trimethyl orthosulfate amino, and the dosage is: 10-15g styrene, 0.8-1.2g methacrylate trimethyl orthosulfate amino.

9. The process for producing a high-adhesion super-hydrophobic protective coating according to claim 1, wherein: The preparation method of step S6: (1) Add hydrophilic nano-SiO2 powder into an ethanol solution containing acetic acid and stir until uniform; (2) adding perfluorotriethoxysilane, dimethoxysilane and ethyl orthosilicate to the above solution system, stirring evenly to obtain a milky white suspension, drying the separated solid substance to obtain a modified super-hydrophobic nano-SiO2 powder, and grinding and debonding with zirconium beads to obtain a super-hydrophobic nano-SiO2 powder; (3) adding super hydrophobic nano-SiO2 powder to limonene solvent and dispersing by ultrasonic, wherein the amount ratio of polymer microspheres to limonene solvent is 1-10 g: 100 mL; (4) adding an equal amount of SEPS super-hydrophobic special adhesive as the nano-SiO2 powder, and mechanically stirring until the adhesive is completely dissolved to obtain a coating solution; (5) uniformly spraying the modified nano-silicon dioxide super-hydrophobic coating on the surface of the film layer, and curing in air to obtain a super-hydrophobic coating. The mass ratio of the SiO2 powder, perfluorotriethoxysilane, dimethoxysilane and ethyl orthosilicate is 6-10: 3-7: 8-12: 8-12.

10. The coating prepared by the method according to any one of claims 1 to 9, characterized in that: The method comprises in sequence a neodymium-modified magnetic nano-iron oxide layer as a steel substrate layer, a negatively-charged modified polymer microsphere membrane layer, a positively-charged modified polymer microsphere membrane layer, and a negatively-charged modified nano-silicon dioxide super-hydrophobic membrane layer.

Citation Information

Patent Citations

  • Preparation method of hollow titanium dioxide microspheres

    CN103359782A

  • Surface cation magnetic polymer microsphere, and preparation method and application thereof

    CN104059204A

  • Construction method of polymer-based super-hydrophobic coating

    CN109836052A

  • Magnetic firm super-hydrophobic surface and preparation method thereof

    CN113634468A

  • Preparation method of super-hydrophobic surface for magnetic control liquid drop lossless transportation

    CN116020725A

Cited By

  • Pre-spraying method for engine cylinder cover and engine cylinder cover

    CN119657439A

  • Anti-corrosion, anti-fouling and anti-drag composite coating as well as preparation method and application thereof

    CN119912856A

  • Super-smooth antifouling anti-drag composite coating with photo-thermal responsiveness and preparation method and application of super-smooth antifouling anti-drag composite coating

    CN119931498A